In the Public Interest : Medical Licensing and the Disciplinary Process - Horowitz, Ruth, 1947- (Book collections on Project MUSE., 2013)
In the Public Interest investigates the mechanisms that democratic societies have used to certify that those working as licensed doctors are properly trained and supervised as they deliver critical services to the public. It analyzes the workings of the crucial public institutions charged with maintaining the safety and legitimacy of the U.S. medical profession and provides prescriptive measures, addresses problems in need of reform, and suggests new procedures, resource allocation, and educat.